Benign Pancreatic Hyperenzymemia (Gullo Syndrome), Histamine Intolerance, and Carbohydrate Malabsorption. Issue 2 (1st April 2017) - Schnedl, Wolfgang J.; Enko, Dietmar; Mangge, Harald; Schenk, Michael; Lackner, Sonja; Holasek, Sandra J.
Abstract : Benign pancreatic hyperenzymemia (Gullo syndrome) is characterized by a more than threefold increase of the pancreatic enzymes lipase and amylase in the absence of a pancreatic disease over a period of more than 1 year, with elevations and significant undulations of pancreatic enzyme serum concentrations occurring on a day-to-day basis for 5 consecutive days. Nonspecific abdominal complaints may be caused by carbohydrate and/or protein malabsorption. We report a patient with benign pancreatic hyperenzymemia with lactose and histamine malabsorption; the symptoms of gastrointestinal malabsorption were treated successfully with an individually tailored lactose- and histamine-free diet.